Podcast: Alternatif Media Dakwah untuk Generasi Digital - Ninda Zahra Wahyudi; Sherly Violeta Fitri; Edi Amin (CV. ULIL ALBAB CORP, 2024)
Da'wah activities are one of the message delivery methods carried out by many religious figures, especially in Indonesia. Sophisticated technology serves as a communication strategy for Da'wah, expanding the audience and target reach. One of them is podcasts, as a medium for delivering communication carried out with a target audience of a more modern and conventional digital generation. We conducted the research using a descriptive-qualitative method, incorporating data collection techniques from literature, book, and journal reviews. The study's findings indicate that podcasts are a popular choice among the digital generation. Podcasts and Da'wah make it easier to reach the expected target or even an audience that is outside the target. The obstacles and challenges faced are the content, which must be interesting, not violate norms, not offend any party, and consistent so that the podcast is popular and heard by the audience.